FILSAFAT PENDIDIKAN ISLAM SUNNI-MADURA (Studi Konsep Pendidikan Islam Masyarakat Sunni-Madura) - Achmad Bahrur Rozi; Misnatun (Wahana Islamika: Jurnal Studi Keislaman, 2020)
The ideal relationship between education and theology should be functional-mutualism so that education has a strong spirit and foundation. As well, theology can have practical and contributory meaning in social life. So education is not just an effort to producing "mechanical" humans who are dry on the values of spirituality and morality, and theology is not merely at the level of the discourse of thinkers. This study is an attempt to construct theological-philosophical thought into a conceptual formula at the educational level. The focus of this study is the construction of the theological-philosophical thought of the Sunni-Madurese community as a unique community entity and religious conception with unique local characteristics as well. Through a philosophical and phenomenological approach it can be concluded that the Sunni-Madurese community is a fiqh-oriented society, more specifically Shafi'iyah fiqh, although it does not completely ignore the esoteric aspects of Sufism. In the context of Islamic transmission, the philosophy of Sunni-Madura tends to avoid the art of preaching. Islamic da'wah in Madura prefers pesantren education pathways so that art becomes an area that is not touched by Islamization. As a society that has a tendency towards fiqh, the philosophy of Sunni-Madura Islamic education emphasizes more on efforts to bring students into human beings who believe, obey worship and obey the shari'ah. So the material taught in pesantren both formal, non-formal, and informal places more emphasis on conceptual mastery and amaliyah (mahdlah) and physical.